Swarm Trapping for Pest Control Operators - Michael K. O'Malley; James D. Ellis; Catherine M. Zettel Nalen (EDIS)
ENY148, a 6-page illustrated fact sheet by M. K. O’Malley, J. D. Ellis, and C. M. Zettel Nalen, outlines the standard operating procedures for swarm trapping by certified Pest Control Operators as a means of capturing and removing a nesting Africanized bee colony before the bees become aggressive. Published by the UF Department of Entomology and Nematology, October 2009.